MODEL STRATEGI PEMBELAJARAN PENDIDIKAN ISLAM BERBASIS WAHYU MEMANDU ILMU - Fadlan Hafiz; Pepen Supendi; Edgardo Kaka Cahyadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine and formulate a learning strategy for Islamic education based on Wahyu Memandu Ilmu (WMI) as an effort to integrate the values ​​of revelation and the development of science in the era of globalization and digitalization. The method used is library research by reviewing various relevant literature, including books, scientific journal articles, and academic documents related to the concept of scientific integration, the epistemology of Islamic education, and learning strategies. The results of the study indicate that the WMI paradigm places revelation as the primary source in the development of science as well as a guideline in the learning process, thereby overcoming the dichotomy between religious knowledge and general knowledge. The WMI-based learning strategy emphasizes the integration of intellectual, spiritual, and moral dimensions through a holistic approach, and is implemented through adaptive and contextual learning methods such as the scientific approach, problem-based learning, and project-based learning. However, its implementation still faces various challenges, including limited understanding of educators, suboptimal development of an integrative curriculum, and minimal systemic support. Therefore, efforts are needed to strengthen educator capacity and reconstruct a curriculum based on scientific integration. Thus, the WMI-based Islamic education learning strategy has significant relevance in developing Islamic education that is holistic, integrative, and oriented towards the formation of perfect human beings.